If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4xy + -5y = -2 Solving 4xy + -5y = -2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5y' to each side of the equation. 4xy + -5y + 5y = -2 + 5y Combine like terms: -5y + 5y = 0 4xy + 0 = -2 + 5y 4xy = -2 + 5y Divide each side by '4y'. x = -0.5y-1 + 1.25 Simplifying x = -0.5y-1 + 1.25 Reorder the terms: x = 1.25 + -0.5y-1
| 10p+15p=5400 | | 3x+(229.84+y)=3039.14 | | 10x-7=101 | | 2x+45=3+7x-8 | | 5x+100=200 | | 2(s+3)=21 | | 5p^2-36p=32 | | (x+4)(6x^3+10x^2-9x+3)= | | 10x+17=3x | | -0.333333333333333x=-0.333333333333333x-0.5 | | 11.74=-log(x) | | 4x-8-2x+3=-10x+7+12x+5 | | 42s+s=8322 | | 4(4x-9)+9x= | | 9x+6(80)=7x+560 | | 6y=-2x | | 8x+9=9x+7 | | 6+3x+4x^2+2x^3=0 | | (6-8i)(6+8i)= | | 3(t-5)-t=7 | | 2x+2y=2809.30 | | 2(5x-6)=4[x-3x+30] | | 100x^2-21=110 | | 4(3x-9)-5=4(x-5)+27 | | 4y^3+27y^2+27=0 | | 27y^2+27=0 | | 3-4*6+3= | | 4(3x-8)-5=4(x-5)+15 | | (11x+26)-3= | | Y^6+9y^4-4y^3+27y^2+27=0 | | -7(2c+5)=(c-6) | | 8y-9=12y+15 |